Women's Communication Strategy for Women's Islamic Organizations in Overcoming Radicalism - Winda Hardyanti (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2023)
Women's involvement in radicalism and their role in addressing the issue are important considerations. Islamic organizations, such as Nahdlatul Ulama (NU) and Muhammadiyah in Indonesia, have played a significant role in combating radicalism. NU has developed the concept of Islam Nusantara as an antidote, while Muhammadiyah focuses on Progressive Islam as a counter-discourse. This research aims to explore the communication strategies used by women activists in Islamic organizations to address radicalism. The study will employ a descriptive qualitative method, focusing on Nasyiatul Aisyiyah and Fatayat NU as mass organizations representing young women. This research have a finding that the women activists in Islamic organizations employ distinct communication strategies to address radicalism, with Muhammadiyah emphasizing moderation and inclusivity, and NU focusing on identifying radicalism within groups. Effective communicators and targeted communication media are prioritized, despite the differing approaches between the two organizations.